Proximate analysis and fatty acid profile Hyophila rosea William and Vesicularia reticulata. - Anuevo, Gwen M.
Philippine mosses number about 506 species. Hyophila rosea Williams and Vesicularia reticulata are the two species that are found abundantly in Panay area., Hyophila rosea Williams are medium sized plants in thin clusters with stems from 1-1.5 cm high. Proximately characterized to contain 17.82 moisture, 5.99 crude protein, 7.69 ether extract, 21.42 crude fiber, 18.21ash and 46.69 nitrogen-free extract. Fatty acid profile are composed of twenty-nine (29) analytes, from which twenty (20) were not identified while nine (9) are known starting from Caproic acid (C10) to Arachidic (C20). Linoleic, palmitic, and oleic acids are the first three analytes comprising higher percentages., Vesicularia reticulata on the other hand, are dull, yellowish green and the main stem is about 5 cm long. Proximately characterized to contain 12.73 moisture, 5.96 crude protein, 9.45 crude ether extract, 21.95 crude fiber, 32.67 ash and 29.96 nitrogen-free extract. Fatty acid profile are composed of forty-one (41) analytes, from which thirty two (32) analytes were not identified while nine (9) analytes are known starting from C10 to C20.Linoleic, palmitic and linolenic acids are the first three analytes comprising higher percentages. Vesicularia reticulata on the other hand, are dull, yellowsih green and the main stem ia about 5 cm. long. Proximately characterized to contain 12.73 percent moisture, 5.96 percent crude protein, 9.45 percent crude ether extract, 21.95 percent crude fiber, 32.67 percent ash and 29.96 percent nitrogen-free extract. Fattyacid profile composed of forty-one (41) analytes, from which thirty (32) analytes were not identified while nine (9) analytes are known starting from C10 to C20. Linoleic, palmitic and linolenic acids are the first three analytes comprising higher percentages.